CHALLENGES IN APPLICATION BASED ACCOUNTING AND FINANCIAL MANAGEMENT PRACTICES FOR MICRO SMALL AND MEDIUM ENTERPRISES - LANTIP SUSILOWATI BINTI SUWADJI (State Islamic Institute (IAIN) Tulungagung, 2023)
Abstract: Many micro, small and medium enterprises (UMKM) have not recorded their business finances so they cannot monitor their business development. For this reason, the purpose of this study is to carry out mentoring activities for micro, small and medium enterprises entrepeneurs in the practice of recording their business finances by using digital applications so that it is simpler and easier to present their financial reports according to SAK EMKM standards. Research that uses a qualitative approach with this type of descriptive research chooses the digital applications chosen to be used are SI APIK and Teman Bisnis because these two applications are easy to access with Android and are quite simple in their practical stages to be practiced with the UMKM community of the Cemoro Barong association, located in Tapan Village, Kedungwaru District, Tulungagung Regency, East Java Province which consists of 18 UMKM with various types of service, trading and manufacturing businesses. As a result, entrepreneurs in the community are enthusiastic about implementing this accounting application. The entrepreneurs can use this application to assist them in controlling merchandise stocks to compiling financial reports according to SAK EMKM standards. This application is suitable for use in recording business finances both services, trade and manufacturing.